Development of trench support system (case study) / Rozaini Abdullah Khairi - Abdullah Khairi, Rozaini (1997)
The main objectives of this project paper is to determine the development of trench support system used in Malaysia. In this case study folly consideration has been emphasized on the type of trench support system traditional and the proprietary support system. Two case studies has been conducted on site, that is in Subang Jaya and also in Sungai Way. These case studies illustrate further the system used, method of installation, the effectiveness of the system and how the selection of the system being made. The data obtained from this questionnaires were used to analyse the development of the trench support system in Malaysia. This study has been based on available reviews from various institution, questionnaires result, on the site interviews with various experts in subject area and also from personal observation on site. From the. survey, 45 questionnaires have been distributed to the public and out of this 18 samples has been received back from respondents.